2022
DOI: 10.3389/fpls.2022.1041068
|View full text |Cite
|
Sign up to set email alerts
|

Joint metabolome and transcriptome analysis of the effects of exogenous GA3 on endogenous hormones in sweet cherry and mining of potential regulatory genes

Abstract: Gibberellin (GA) is an important phytohormone that can participate in various developmental processes of plants. The study found that application of GA3 can induce parthenocarpy fruit and improve fruit set. However, the use of GA3 affects endogenous hormones in fruits, thereby affecting fruit quality. This study mainly investigates the effect of exogenous GA3 on endogenous hormones in sweet cherries. The anabolic pathways of each hormone were analyzed by metabolome and transcriptome to identify key metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Poulev et al using liquid chromatography/mass spectrometry (LC/MS) analysis compared the tricin content and some additional avonoid compositions of rice bran samples from different color pericarp genotypes, and found that the purple pericarp genotype had higher levels of tricin, as well as a wider range of avonoid types [43], indicating that the tricin content might be involved in regulating the expression of the color of the purple pericarp of rice bran. To study the molecular mechanisms underlying the different colors of cherry fruits, multi-omics analysis of plants revealed that the transcription factors SBP, bHLH, WD40, and bZIP may regulate the accumulation of avonoids such as hesperidin and naringenin and thus be involved in the coloration of yellow sweet cherry fruits during the second stage of the coloration process, which is from green to yellow [44]. This suggests that quercetin is also related to the coloration of cherry fruits.…”
Section: Structural Analysis Of the Mdpc Gene And Its Putative Functi...mentioning
confidence: 99%
“…Poulev et al using liquid chromatography/mass spectrometry (LC/MS) analysis compared the tricin content and some additional avonoid compositions of rice bran samples from different color pericarp genotypes, and found that the purple pericarp genotype had higher levels of tricin, as well as a wider range of avonoid types [43], indicating that the tricin content might be involved in regulating the expression of the color of the purple pericarp of rice bran. To study the molecular mechanisms underlying the different colors of cherry fruits, multi-omics analysis of plants revealed that the transcription factors SBP, bHLH, WD40, and bZIP may regulate the accumulation of avonoids such as hesperidin and naringenin and thus be involved in the coloration of yellow sweet cherry fruits during the second stage of the coloration process, which is from green to yellow [44]. This suggests that quercetin is also related to the coloration of cherry fruits.…”
Section: Structural Analysis Of the Mdpc Gene And Its Putative Functi...mentioning
confidence: 99%
“… ( A ) The biosynthetic pathway of gibberellin (GA) in sweet cherry. The GA pathway is based on the study of Chen et al [ 4 ]. ( B ) Visual heatmap of gene expression of gibberellin-related enzymes in the fruit of sweet cherry.…”
Section: Figurementioning
confidence: 99%
“…GA is an important plant hormone and signaling pathway factor that plays an important role in plant growth and development and stress resistance environment [ 4 ]. Studies have shown that GA treatment can induce parthenogenesis to increase the fruit-setting rate and thus increase fruit yield.…”
Section: Introducementioning
confidence: 99%
“…In Prunus avium, the application of gibberellin 3 (GA3) can induce parthenogenetic fruit and increase fruit setting rate, but it will affect the endogenous hormones and quality in fruit. Transcriptome analysis of the spontaneous early ripening of a navel orange mutant and wild type revealed that a large number of differentially expressed genes (PP2C, SnRK, JAZ, ARF, PG and PE) were involved in plant hormone signal transduction and starch and sucrose metabolism, indicating the importance of these metabolic pathways in fruit ripening [26][27][28][29]. The transition from vegetative growth to reproductive growth is a major stage change in plants.…”
Section: Introductionmentioning
confidence: 99%